An Absence of Nuclear Lamins in Keratinocytes Leads to Ichthyosis, Defective Epidermal Barrier Function, and Intrusion of Nuclear Membranes and Endoplasmic Reticulum into the Nuclear Chromatin - Jung, Hea-Jin (Mol Cell Biol, 2014)
B-type lamins (lamins B1 and B2) have been considered to be essential for many crucial functions in the cell nucleus (e.g., DNA replication and mitotic spindle formation). However, this view has been challenged by the observation that an absence of both B-type lamins in keratinocytes had no effect on cell proliferation or the development of skin and hair. The latter findings raised the possibility that the functions of B-type lamins are subserved by lamins A and C. To explore that idea, we created mice lacking all nuclear lamins in keratinocytes. Those mice developed ichthyosis and a skin barrier defect, which led to death from dehydration within a few days after birth. Microscopy of nuclear-lamin-deficient skin revealed hyperkeratosis and a disordered stratum corneum with an accumulation of neutral lipid droplets; however, BrdU incorporation into keratinocytes was normal. Skin grafting experiments confirmed the stratum corneum abnormalities and normal BrdU uptake. Interestingly, the absence of nuclear lamins in keratinocytes resulted in an interspersion of nuclear/endoplasmic reticulum membranes with the chromatin. Thus, a key function of the nuclear lamina is to serve as a “fence” and prevent the incursion of cytoplasmic organelles into the nuclear chromatin.